An Analysis of Energy Consumption In The Goverment Buildings’ In Indonesian Border - Syarifudin Syarifudin; Andrial Imran (Jurnal Indonesia Sosial Teknologi, 2024)
In this research, energy consumption analysis was conducted at the Main building regent’s office of nunukan. The analysis was conducted on the main variables of energy efficiency, namely: measurement of temperature and relative humidity, calculation of Overall Thermal Transfer Value (OTTV) and Roof Thermal Transfer Value (RTTV), calculation of Energy Consumption Intensity (IKE) in air-conditioned and non-air-conditioned rooms as well as an analysis of opportunities to increase the efficiency of energy consumption in the buildings.. Based on the calculation and result of IKE in both buildings, they are still considered in the category of EFFICIENT. However, based on the measurement of temperature and relative humidity, it shows that in both buildings air conditioning is still necessary to achieve the level of thermal comfort, therefore an increase of efficiency in the load is needed to avoid wastage.